Losing control: Comparing the role of personality during two types of stressful life experiences. (1st April 2020) - Sweeny, Kate; Howell, Jennifer L.; Kwan, Victor W.
Highlights: We compared the role of personality in stressful preparation and waiting periods. Two longitudinal studies examined real-world stressful experiences. Neuroticism predicted negative emotions more strongly when preparing vs. waiting. Abstract: We compared the role of personality (neuroticism, conscientiousness, and dispositional optimism) during stressful preparation and waiting periods. Study 1 compared the role of personality in the experience of undergraduate students ( N  = 120) preparing for and awaiting their grade on a midterm exam in a 1-week longitudinal study. Study 2 extended this investigation to a sample of law school graduates ( N  = 201) taking the bar exam in a 4-month longitudinal study. Across studies, multilevel models nesting stressor phase (preparing vs. waiting) within person revealed that neuroticism was tied more strongly to negative emotions when preparing than when waiting. Our findings suggest that stressful experiences that confer a degree of control may enhance the role of emotion-relevant traits on responses to such stressors.